Fifth Five-Year Plan Draft Annual Plan 1974-75 Volume II (Statements) Government of Bihar - Planning Commission (Planning Commission, 1973)
Sectoral Statement (financial) Sectoral Programmes (Financial outlay) Agriculture & Applied Programmes Agricultural Education and Research Crop Husbandly Area Development Programme and Projects and Programmes of Rural Development & Employment Land Reforms Minor Irrigation Soil Conservation Animal Husbandry Dairying & Milk Supply Forests Fisheries Agricultural Marketing Warehousing & Storage.
Government of Bihar, Planning Department